2022
DOI: 10.1038/s44159-022-00056-w
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and shaping the future of work with self-determination theory

Abstract: Self-determination theory has shaped our understanding of what optimizes worker motivation by providing insights into how work context influences basic psychological needs for competence, autonomy and relatedness. As technological innovations change the nature of work, self-determination theory can provide insight into how the resulting uncertainty and interdependence might influence worker motivation, performance and well-being. In this Review, we summarize what self-determination theory has brought to the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 213 publications
3
72
1
Order By: Relevance
“…In other words, when autonomy, competence and relatedness are met in the workplace, higher levels of commitment, job satisfaction, and employee motivation can be observed among organization members. 76,77 This partially corroborates the findings of Marshall, 87 who demonstrated that empowerment does not influence job stress. The contradictions detected in the academic literature may be explained by the context in which the research was conducted, as detailed in the next section.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…In other words, when autonomy, competence and relatedness are met in the workplace, higher levels of commitment, job satisfaction, and employee motivation can be observed among organization members. 76,77 This partially corroborates the findings of Marshall, 87 who demonstrated that empowerment does not influence job stress. The contradictions detected in the academic literature may be explained by the context in which the research was conducted, as detailed in the next section.…”
supporting
confidence: 87%
“…Finally, Gagné et al 77 stated that increasing levels of psychological empowerment in the workplace, particularly self-determination, requires that autonomy, competence, and relatedness are met. 77 However, the findings of present research indicate that job stress levels can also be reduced when perceived autonomy is achieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapidly evolving (hybrid) school environment can benefit from teachers' adaptive and proactive performance behaviours (Collie et al, 2020), as such an environment is characterised by uncertainty. In uncertain or unpredictable environments, adaptability and proactivity matter more than proficiency (Gagné et al, 2022;Griffin et al, 2007), and the current study illustrates how this can be achieved.…”
Section: Discussionmentioning
confidence: 79%
“…The individual's motivation is deeply rooted in the Self-Determination Theory-SDT [22,23]. It is a widely accepted theory applied in various fields (e.g., education, healthcare, sports) as well as in organisational management [24].…”
Section: Work Motivationmentioning
confidence: 99%